Human Resources Accounting and its Impact on Organizational Justice Field Research in the Ministry of Education - et. al., Prof. Dr. Ghani Dahham Al-Zubaidi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to determine the impact of human resources accountability on organizational justice, and the research problem was embodied by the lack of interest in human resources accountability, which was reflected in organizational justice in the Ministry of Education. The descriptive analytical approach, and the research community included directors of departments and divisions at the headquarters of the Ministry of Education, and the sample size was (224) individuals from the total community of (533) , And adopted a questionnaire as a main tool for collecting data and information, in addition to the interviews that Conducted by the researcher , To analyze the results of the field research, the researcher adopted a program Spss.v26)), and the search included Main hypothesis and (7) sub hypotheses represented by influence relationships , And the data were processed statistically according to aMultiple statistical methods, including (the arithmetic mean, and the standard deviation) , Simple linear regression), and the results of the research led to the acceptance of all alternative hypotheses and the rejection of null hypotheses.that There is a weak interest in human resource accounting , and surely over there Effect Important toAccountability of human resources in organizational justice in the Ministry of Education.